Efetividade da auriculoterapia na dor e ansiedade de parturientes: ensaio clínico randomizado - Silva Neto, Fernando Soares da (2023)
Among the most recent contexts of care and humanization, Integrative Practices have been gaining ground and becoming a way of helping women within the pregnancy-puerperal cycle. Practices such as aromatherapy, auriculotherapy, music therapy, massages, reflexology and floral remedies have been increasingly used and studied in the care of women during pregnancy, childbirth and the postpartum period in various outcomes. The use of PICs is very relevant, as it provides an alternative way of minimizing discomfort and promoting improvements in health conditions, from a holistic and humanistic perspective. This dissertation is structured in two stages: the first is a methodological investigation, which sought to summarize scientific studies on the use of integrative and complementary practices (PICs) in the management of pain in parturient women. To this end, a Systematic Review was carried out. 17 studies were included, which evaluated 2,371 women. The use of massage therapy and acupuncture stood out in terms of pain management during labor. There was no homogeneity between therapeutic application protocols. Four studies obtained a high risk of viruses and 13 a low risk of viruses. PICs prove to be a viable, easy-to-manage and effective alternative to labor pain when compared to usual care and/or placebo. The second stage involved the development of a Clinical Trial, randomized, controlled, with two arms, which proposed to evaluate the effectiveness of using auriculotherapy in the pain and anxiety of women in labor. Women attending the Instituto Cândida Vargas – ICV, admitted to the Obstetric Center, in active labor were recruited. Data collection was carried out with the application of pre- and post-intervention questionnaires and scales associated with the research scenario. A significance level of 5% was set for all variables. The research follows ethical precepts with approval by CEP Opinion: (5,722,961) and ReBEC obtaining approval number RBR-6gpvcvr. The average age in the intervention group was 26.01 years and in the control group 25.51 years. The majority of parturients in the intervention (62- 75.6%) and control (71-79.8%) declared themselves non-white, that is, brown, black, indigenous and/or yellow. A progressive increase in average pain was observed in the control group compared to the intervention. Regarding anxiety, there is a pattern of slight increase on the anxiety scale in the control group during the 2 hours of observation, while the intervention group observes a decrease. Data analysis showed that pain and anxiety scores after 120 minutes are statistically significant (p-value <0.05) for both the intervention and control, however, with an increase in the mean and median of pain and anxiety in the control group, and with a decrease in the mean and median in the GI. The relative risk for auriculotherapy is 2.29, with a number needed to treat (n=03) and anxiety is 79.3% in the intervention and 61.8% in the control, presenting a relative risk for not worsening of 1.62, and a number necessary to treat (n=06). The comparison analysis of pain and anxiety after the application of auriculotherapy showed a statistically significant reduction in pain and anxiety in the intervention group when compared to the control, both when comparing medians and when comparing the proportion of women who achieved maintenance or improvement in pain and anxiety during labor in both groups. From the analysis it can be concluded that auriculotherapy is significantly effective in stabilizing and improving pain and anxiety during labor.